Study of aeration performance of open channel chutes equipped with a flip bucket - Emiro?lu, M. Emin; Baylar, Ahmet (My University, 2003)
An adequate supply of dissolved oxygen (DO) is essential for the survival of aquatic organisms. Hydraulic structures can increase DO levels by creating turbulent conditions where small air bubbles are carried into the bulk of the flow. The flip bucket on open channel chutes with mild slopes is a particular instance of this, although the aeration performance of such structures has not been studied in the laboratory and field. This paper considers flip bucket chutes with different inclination angles and lip angles and how they affect aeration performance. It is demonstrated that the aeration efficiency of chutes with flip buckets is better than for those without.
Keywords: Aeration efficiency; Chute; Dissolved oxygen; Flip bucket; Open channel; Oxygen transfer